Elevated levels of urinary hydrogen peroxide, advanced oxidative protein product (AOPP) and malondialdehyde in humans infected with intestinal parasites - Chandramathi, S.; Suresh, K.; Anita, Z.B.; Kuppusamy, U.R. (2009)
Oxidative stress has been implicated as an important pathogenic factor in the pathophysiology Of various life-threatening diseases such as cancer, cardiovascular diseases and diabetes. It occurs when the production of free radicals (generated during aerobic metabolism, inflammation, and infections) overcome the antioxidant defences in the body. Although previous Studies have implied that oxidative stress is present in serum of patients with parasitic infection there have been no Studies confirming oxidative stress levels in the Malaysian population infected with intestinal parasites. Three biochemical assays namely hydrogen peroxide (H(2)O(2)), lipid peroxidation (LP) and advanced oxidative protein product (AOPP) assays Were carried out to measure oxidative stress levels in the urine of human subjects whose stools,were infected with parasites Such as Blastocystis hominis, Ascaris, Trichuris, hookworm and microsporidia. The levels of H(2)O(2), AOPP and LP were Significantly higher (P<0.001, P<0.05 and P<0.05 respectively) in the parasite-infected subjects (n = 75) compared to the controls (n = 95). In conclusion, the study provides evidence that oxidative stress is elevated in humans infected by intestinal parasites. This study may influence future researchers to consider free radical-related pathways to be a target in the interventions of new drugs against parasitic infection and related diseases.